2021
DOI: 10.3390/ma14133692
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gd3+ Substitution on Thermoelectric Power Factor of Paramagnetic Co2+-Doped Calcium Molybdato-Tungstates

Abstract: A series of Co2+-doped and Gd3+-co-doped calcium molybdato-tungstates, i.e., Ca1−3x−yCoy▯xGd2x(MoO4)1−3x(WO4)3x (CCGMWO), where 0 < x ≤ 0.2, y = 0.02 and ▯ represents vacancy, were successfully synthesized by high-temperature solid-state reaction method. XRD studies and diffuse reflectance UV–vis spectral analysis confirmed the formation of single, tetragonal scheelite-type phases with space group I41/a and a direct optical band gap above 3.5 eV. Magnetic and electrical measurements showed insulating behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…However, its value significantly increases with increasing temperature, i.e., in the intrinsic region above 300 K for a sample richer in neodymium ions, regardless of the crystallographic direction. Similar behavior of S 2 σ(T) with only a few fW/(cmK 2 ) was observed in ceramic Gd 3+ and Co 2+ -co-doped calcium molybdato-tungstates [ 46 ] as well as in Nd 3+ and Mn 2+ -co-doped calcium molybdato-tungstates [ 47 ]. The above mentioned studies show that even in ion-bonded materials containing a constant content of 3 d transition metal ions, thermoelectric efficiency can be improved by doping them with 4 f rare-earth ions.…”
Section: Resultssupporting
confidence: 63%
“…However, its value significantly increases with increasing temperature, i.e., in the intrinsic region above 300 K for a sample richer in neodymium ions, regardless of the crystallographic direction. Similar behavior of S 2 σ(T) with only a few fW/(cmK 2 ) was observed in ceramic Gd 3+ and Co 2+ -co-doped calcium molybdato-tungstates [ 46 ] as well as in Nd 3+ and Mn 2+ -co-doped calcium molybdato-tungstates [ 47 ]. The above mentioned studies show that even in ion-bonded materials containing a constant content of 3 d transition metal ions, thermoelectric efficiency can be improved by doping them with 4 f rare-earth ions.…”
Section: Resultssupporting
confidence: 63%
“…Therefore, the size effect, in this case, has a decisive influence on the increase of the power factor, since the volume of the unit cell (V ) increases with the increase of the vanadium content (x) in the sample (Table I) despite the fact that the vanadium ion (V 5+ ) substituted for ytterbium one (Yb 3+ ) has a smaller ion radius [24]. A similar size effect on the thermoelectric power factor was observed in the case of cobalt and gadolinium-doped calcium molybdato-tungstates [25]. It is well known that the materials with a large power factor value have the most promising thermoelectric properties, especially if they are heavily doped semiconductors, such as Bi 2 Te 3 [26].…”
Section: Electrical Propertiesmentioning
confidence: 59%
“…No intrinsic region in the relation, σ(10 3 /T), was also observed among others in Ca 1−x Mn x (MoO 4 ) 0.50 (WO 4 ) 0.50 ceramics, 13 Ca 1−x Mn x MoO 4 nanomaterials, 12 CdRE 2 W 2 O 10 tungstate mi crocrystals (RE = Y, Nd, Sm, and Gd−Er), 42 and Ca 1−3x−y Co y □ x Gd 2x (MoO 4 ) 1−3x (WO 4 ) 3x molybdato-tungstate micropowders. 14 Residual electrical conductivity of the ptype up to 230 K and the n-type above this temperature (Figure 7) in the extrinsic region seem to be related to the presence of a small amount of cationic and anion vacancies in the studied single crystals. Another explanation may be related to the fact that at a state of thermal equilibrium structural defects (n) are always present in the lattice even in a crystal which is ideal in other respects.…”
Section: ■ Introductionmentioning
confidence: 91%
“…Our previous studies of calcium molybdate nanomaterials doped with Mn 2+ ions 12 and calcium molybdato-tungstate microcrystals doped with Mn 2+ 13 or Co 2+ and Gd 3+ 14 ones have generally shown that they are nonconductive diamagnets or paramagnetics with a spin-only contribution for molybdates and a spin–orbit coupling for molybdato-tungstates. In these materials, a relatively low value of dielectric permittivity at low frequencies was observed, which is characteristic for space charge polarization.…”
Section: Introductionmentioning
confidence: 99%